2002
DOI: 10.1046/j.1365-2559.2002.01328.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical markers in the differentiation of thymic and pulmonary neoplasms

Abstract: Staining for TTF-1, CD5 and CD1a have potential use in distinguishing between pulmonary and thymic neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 30 publications
2
29
1
Order By: Relevance
“…Previous studies reported CD5-positive rates of 50-100%, 9,8,11,33 however, our study shows the lower CD5-positive rate (33%). This would be explained by a smaller tissue of tissue microarray.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Previous studies reported CD5-positive rates of 50-100%, 9,8,11,33 however, our study shows the lower CD5-positive rate (33%). This would be explained by a smaller tissue of tissue microarray.…”
Section: Discussioncontrasting
confidence: 80%
“…It is sometimes difficult to make the differential diagnosis between thymoma type B3 and thymic carcinoma histologically, especially when the biopsy specimen is small. Although immunoreactivity for CD5 and c-kit has been reported as a useful marker for primary thymic carcinoma, but not for thymoma, the positive rate of CD5 and c-kit has been reported to be limited to over 50%; [3][4][5][6][7] and as not all neoplastic cells in thymic carcinomas stain positive for these markers, [8][9][10][11] it will be necessary to identify other diagnostic markers to make the differential diagnosis more reliable.…”
mentioning
confidence: 99%
“…Previously, the association of presumed antigenpresenting cells, which are immunohistochemically positive for CD1a and S100 protein, in thymic neoplasms was investigated (8)(9)(10). However, it was subsequently established that CD1a and S100 protein are not specific markers for antigenpresenting cells.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry (IHC) may be helpful in select cases. Thymic carcinoma (non-NEC types) may express CD5 and/or CD117 (c-kit), markers that are not typically seen in carcinomas of the lung [16,17]. TTF-1 may be helpful in distinguishing NEC of pulmonary origin [1].…”
Section: Other (Specify)mentioning
confidence: 99%
“…ii. Excluding other potential primary sites of origin from thymic carcinoma[16][17][18]. Although best done clinically, the exclusion of metastatic carcinoma to the mediastinum may be facilitated by the use of immunohistochemical stains for CD5 and c-KIT (CD117).…”
mentioning
confidence: 99%